Interpersonal Communication Between PT. Employment Services Distributors and Prospective Migrant Workers During Recruitment (Case Study of Ms. YH as a Representative of Illegal Services Distributors and Ms. EE as a Former Migrant Worker) - Sudirman, Ermila Rizka; Taubih, Lalu Ahmad (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
Recruitment carried out by PT labor service providers is still carried out today in Sumbawa Regency. The main problem in this research is how service distributors succeed in convincing prospective migrant workers to work as household assistants abroad. The theory used in this research is interpersonal communication theory by Joseph A Devito in 1989. The research method used in this research is a qualitative method and data collection techniques using observation of the situation and environmental conditions where the informants live and interviewing research informants directly and the objectives of This research is to determine the interpersonal communication used by PT labor service providers to prospective migrant workers during recruitment. And the results of this research show that there is an attitude of openness carried out by PT service providers towards prospective migrant workers. Empathy is in the form of actions carried out by PT service providers to prospective migrant workers. Support in the form of assistance and materials provided by PT service providers to prospective migrant workers. A positive feeling in the form of respect and listening is given by PT service providers when interacting with prospective migrant workers, and finally there is no equality in communication between PT service distributors and prospective migrant workers.